The Awkward Homecoming of Maria Monk: Printers, Censors, and a Mysterious Canadian Edition of an Anti-Catholic Best-Seller - Pass, Forrest (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada, 2024)
Awful Disclosures of Maria Monk (1836) is perhaps Canada's most scandalous literary export. However, only a few editions of the scurrilous anti-Catholic fabrication have been published in its purported author's country of origin. A mysterious undated edition, “published for the trade” in Toronto, is probably the most widely circulated Canadian printing. Based on a close investigation of the Toronto edition's physical characteristics—the stereotype plates used to print it, the illustrations, and the mismatched printer's ornaments appearing on certain pages—as well as the ownership history of one copy and the context of the book's legal status in Canada, this article argues that the Toronto edition is evidence of an anonymous publisher's strategies to evade customs censorship. It suggests that these strategies influenced how Canadian readers might have engaged with Awful Disclosures, highlighting the tension between obscenity and anti-Catholicism that underlay the book’s reception among readers, printers, and censors.